Optimalisasi Proses Klaim Asuransi Protection & Idemnity (P&I) pada Kecelakaan Kerja Crew di Kapal PT Pertamina International Shipping - Ngazizah Nuraini; Yustiani Frastika; Iksan Saifudin; Jeihn Novita C. Budiman; Frisca Mareyta Pongoh (Politeknik Pelayaran Sulawesi Utara, 2024)
Film is one of the mass communication media that has a significant power in delivering messages to audiences. As a form of art and entertainment, film not only serves as a means of recreation but also as a tool for conveying values, ideologies, and social criticism to society. This study aims to analyze the representation of women's power in the film Jangan Salahkan Aku using Roland Barthes' semiotic approach. The analysis is conducted using the concept of lexia and Barthes' five reading codes, namely the hermeneutic, proairetic, symbolic, cultural, and semic codes. The findings indicate that women's power in this film is represented through narrative and visual elements that emphasize women's positions in power relations, both in domestic and social spheres. This study contributes to understanding how cinema constructs and reflects the representation of women's power through a complex system of signs.